Application Level Security in a Public Library: A Case Study. - Thomchick, Richard; San Nicolas-Rocca, Tonia (Information Technology & Libraries, 2018)
Libraries have historically made great efforts to ensure the confidentiality of patron personally identifiable information (PII), but the rapid, widespread adoption of information technology and the internet have given rise to new privacy and security challenges. Hypertext Transport Protocol Secure (HTTPS) is a form of Hypertext Transport Protocol (HTTP) that enables secure communication over the public internet and provides a deterministic way to guarantee data confidentiality so that attackers cannot eavesdrop on communications. HTTPS has been used to protect sensitive information exchanges, but security exploits such as passive and active attacks have exposed the need to implement HTTPS in a more rigorous and pervasive manner. This report is intended to shed light on the state of HTTPS implementation in libraries, and to suggest ways in which libraries can evaluate and improve application security so that they can better protect the confidentiality of PII about library patrons.